Innovation strategies in sports management: COVID-19 and the Latin American tennis federations - Crespo Celda, M.; Botella-Carrubi, D.; Jabaloyes, J.; Simón-Moya, V. (Academia Revista Latinoamericana de Administracion, 2022)
Purpose: The purpose of this paper is to discuss some of the most relevant innovation strategies used by the Latin American national tennis federations as a response to the COVID-19 pandemic. Design/methodology/approach: The methodology consists of a survey. The survey consisted of three sections apart from the consent one: a general descriptive part, one with 30 questions to assess attitudes and perceptions and a final section which included open questions. After the data were collected, the SPSS software was used to test the distribution of the sample. Findings: Results show that executives' perception toward their need for involvement in the decision-making process varies. Research limitations/implications: The first limitation relates to the sample size of executives who completed the questionnaire. The second limitation refers to the details provided in the open section of the questionnaire. Specifically, the space allocated for the answers and the degree of detail required could have been optimized by providing further instructions on the importance of facilitating information related to the implementation of the programs. Practical implications: The results demonstrate that, although traditional management, organizational and administrative behaviors are still present in the tennis ecosystem, a more innovative mentality should embed these organizations. It is then relevant that sport and tennis organizations commit to the implementation of innovative strategies for the optimization of the administration of their ecosystems. Originality/value: The paper adds more understanding to the brand of sports management. Furthermore, the fact of developing the study in a COVID-19 context sheds light on the issues faced by sports in a pandemic like this one.